2018
DOI: 10.1136/oemed-2018-105162
|View full text |Cite
|
Sign up to set email alerts
|

Ambient concentrations of NO2 and hospital admissions for schizophrenia

Abstract: ObjectivesSchizophrenia is a chronic and severe mental disorder affecting more than 21 million people worldwide. Short-term exposure to nitrogen dioxide (NO2) has been associated with hospital admissions (HAs) for mental disorders, but no study has evaluated the specific association of NO2 and schizophrenia. Additionally, the shape of the concentration–response (C–R) curve has not yet been assessed at present. This study aims to investigate the relationship between short-term exposure to NO2 and HAs for schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Recent time-series studies have documented associations between short-term, city-level air pollution concentrations and daily hospital admissions for schizophrenia and depression. 21 , 22 We build on this research in several ways. Our air pollution data achieve high spatial precision, thereby reducing potential exposure misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent time-series studies have documented associations between short-term, city-level air pollution concentrations and daily hospital admissions for schizophrenia and depression. 21 , 22 We build on this research in several ways. Our air pollution data achieve high spatial precision, thereby reducing potential exposure misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypothesis, we did not find a positive association between most of the air pollutants considered in our study, such as PM 10 , PM 2.5 , CO and NO 2 . This is in contrast with previous literature on this subject (Szyszkowicz et al ., 2009, 2010, 2018; Mehta et al ., 2015; Power et al ., 2015; Chen et al ., 2018; Duan et al ., 2018; Eguchi et al ., 2018; Kim et al ., 2018; Oudin et al ., 2018; Shin et al ., 2018; Song et al ., 2018; Bai et al ., 2019; Lee et al ., 2019; Qiu et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, long-term exposure to ambient air pollution could be an independent risk factor for mental health disorders ranging from subjective stress to depressive disorders and suicidal ideation (Shin et al ., 2018). Recent studies analysing the association between daily levels of air pollutants and hospital admissions for mental disorders showed significant results for different pollutants considered both for admissions for generic mental disorders (Chen et al ., 2018; Kim et al ., 2018; Song et al ., 2018; Lee et al ., 2019; Qiu et al ., 2019) and for specific diagnoses such as schizophrenia (Gao et al ., 2017; Duan et al ., 2018; Bai et al ., 2019), depression (Szyszkowicz et al ., 2016; Wang et al ., 2018) and substance abuse (Szyszkowicz et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that both biological factors such as neuroinflammation as well as psychosocial factors such as mental stress may be relevant mechanisms to explain the increased risk of psychotic experiences due to air pollution. A recent Chinese study also demonstrated an increased RR of hospitalizations due to schizophrenia (1.10, 95% CI 1.01–1.18 per IQR increase) due to increased short-term exposure to NO 2 [ 113 ].…”
Section: Evidence From Human and Animal Studiesmentioning
confidence: 99%